2022
DOI: 10.1111/cogs.13208
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the What and When of Analogical Reasoning Across Analogy Formats: An Eye‐Tracking and Machine Learning Approach

Abstract: Starting with the hypothesis that analogical reasoning consists of a search of semantic space, we used eye-tracking to study the time course of information integration in adults in various formats of analogies. The two main questions we asked were whether adults would follow the same search strategies for different types of analogical problems and levels of complexity and how they would adapt their search to the difficulty of the task. We compared these results to predictions from the literature. Machine learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
(166 reference statements)
1
4
0
Order By: Relevance
“…As in Duncan et al's (2017) study, the majority of errors in both Combined and Separated conditions were "wrong alternatives," that is, drawing the alternative feature that was presented in the matrix, but was not the correct response feature. This might suggest that the children were easily confused when selecting which features to attend and select from cells A, B, or C, and is consistent with the broader literature on children's problem-solving skills, suggesting that children do not systematically orient and organise their searches across the cells in matrix reasoning problems and analogical reasoning more generally (Chen et al, 2016;Glady et al, 2012Glady et al, , 2017Starr et al, 2018;Thibaut & French, 2011;Vendetti et al, 2017). While the Separated format reduced errors of all types, and did not induce a qualitatively different pattern of errors, it appeared particularly beneficial in reducing the most common "wrong alternative" errors.…”
Section: Discussionsupporting
confidence: 77%
“…As in Duncan et al's (2017) study, the majority of errors in both Combined and Separated conditions were "wrong alternatives," that is, drawing the alternative feature that was presented in the matrix, but was not the correct response feature. This might suggest that the children were easily confused when selecting which features to attend and select from cells A, B, or C, and is consistent with the broader literature on children's problem-solving skills, suggesting that children do not systematically orient and organise their searches across the cells in matrix reasoning problems and analogical reasoning more generally (Chen et al, 2016;Glady et al, 2012Glady et al, , 2017Starr et al, 2018;Thibaut & French, 2011;Vendetti et al, 2017). While the Separated format reduced errors of all types, and did not induce a qualitatively different pattern of errors, it appeared particularly beneficial in reducing the most common "wrong alternative" errors.…”
Section: Discussionsupporting
confidence: 77%
“…Gaze behaviors are a promising source of information on cognitive development, including the development of flexible problem solving because, they can be gathered across ages, and do not exclude young children with poor motor control and eye-hand coordination. Looking-time measures have often been used in psychological research to investigate the early and lifespan development of cognitive capacities (e.g., Baillargeon 2004;Eckstein et al 2017;Krøjgaard et al 2020;Onishi and Baillargeon 2005;Thibaut et al 2011). Looking-time measures may be collected even in the first days of life, offering early insight into developmental changes in attention.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Increases in knowledge may also support such generalization, but it is unlikely that only 14-year-olds would have conceptual knowledge sufficient for transferring simple relations, such as "X fits in Y" across simple items that differ in colors and shapes. Eightyear-olds' disadvantage may instead result from poorer use of executive functions than 14-year-olds' (Thibaut et al 2011;Thibaut and French 2016). Thibaut and French (2016) showed that 8-year-olds focus more on the C item and less on the A:B pair than adults, suggesting that, compared to 14-year-olds, 8-year-olds may have greater difficulties in inhibiting the ultimate goal of the task (studying C to find the correct D) in favor of the currently relevant subgoals (studying the relationship between A and B; drawing the relationship between C and potential Ds), and switching between the ultimate goal and the subgoals (see also French et al 2017 for a modelling approach).…”
Section: Complex Transfersmentioning
confidence: 99%
See 1 more Smart Citation
“…Relational attention may shift with a reasoner’s expertise in the relevant knowledge-base, which changes the nature of reasoners’ attention to the relational content of a task ( Chi et al, 1981 ). As knowledge increases, reasoners may shift from attention to surface features and object-level correspondences to relational correspondences (see Gentner, 1988 ; Starr et al, 2018 ; Thibaut et al, 2022 ).…”
Section: Relationship Between Efs and Relational Reasoningmentioning
confidence: 99%